Examining Corporate Engagement in Social Media: Advancing The Use of Facebook for Corporation Page - Arif Nugroho; Anna Agustina (Fakultas Ilmu Komunikasi Universitas Pancasila, 2020)
This article focuses on the engagement conducted through Facebook fan page. Analyzing responses of customer to the postings made by corporate user will give input on what need to be put in attention and revise to meet the need of customers. The need to put more attention on details of social media feature becomes essentials in advancing engagement through –in this case- Facebook. The aim of the study is to identify highest engagement items in Facebook feature by examining Telkomsel Facebook page postings as a case. The data is content in Telkomsel Facebook. Data collection used Facebook-graph data mining technique. Media content analysis method conducted to analyze all the data using engagement concept. The study found 7 items that have the highest engagement rate on Facebook, which are: visual indicator in the form of video (1), 200 characters on Facebook texts (2), information with corporate brand, Telkomsel, on it (3); entertainment content (4), a call to action message to engage fans, such as quiz (5); high engagement happened in weekdays (6), to the multiple postings (7), and posting hours is in peak hours (8.00 – 17.00).